A SOCIO PRAGMATIC ANALYSIS OF SPEECH ACT OF MALE AND FEMALE CHARACTER IN TO ALL THE BOYS: ALWAYS AND FOREVER MOVIE - Astin Leuisa Maysafira; Aris Hidayatulloh (Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze speech acts in the context of sociolinguistic aspects with a focus on language interaction. Speech act is a form of verbal expression that has social impact and pragmatic meaning in daily human communication. This research focuses on the types and factors in speech acts that exist in the two male and female leads in the movie entitled To All The Boys: Always and Forever. Through a sociolinguistic and descriptive qualitative approach, this research explores the relationship between speech acts and social dynamics in various communication situations. This research method involves collecting data from the speech acts in the scripts of the movie. The data were then analyzed qualitatively by considering the speech act framework as well as concepts in sociolinguistic theory. The analysis shows that speech acts play an important role in representing gender norms in society. Language choices, speaking styles, and the types of speech acts used can differ based on gender, reflecting the social construction of gender roles. However, this cannot be a stereotype in everyday social life to categorize gender. Therefore, the author adds the aspect of types and factors behind the purpose of a conversation between men and women.